Synthesis of p-methoxyphenacylmethacrylate - Soykan, C; Özdemir, E; Ahmedzade, M (Elsevier Science Bv, 2001)
p-Methoxyphenacylmethacrylate (MPMA) was prepared from p-methoxyphenacylbromide and sodium methacrylate. Polymerization of the monomer was carried out in 1,4-dioxane solution in presence of 2,2'-azobisisobutyronitrile as an initiator at 70 degreesC. The monomer and the polymer microstructure were investigated by FT-IR, H-1-NMR and C-13-NMR techniques. The oxime and hydrazone derivatives of poly(MPMA) were also prepared and characterized by FT-IR, TGA and DSC. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: p-methoxyphenacylmethacrylate; oxime; hydrazone